The Influence Of Entrepreneurial Learning On Interest In Entrepreneurship Students Of The Master's Institute Of Technology And Business - dwiputri, Ikanov; Firmananda, Fahmi Iqbal; Yasra, Dewi (EL-EMIR Institute, 2024)
The study aims to investigate the extent to which entrepreneurship learning affects student entrepreneurship interest of management degree and accountancy degree program of Master’s Institute of Technology and Business.The study uses quantitative methods. The research variables were entrepreneurship learning as the independent variable and entrepreneurship interest as the dependent variable. The data that used in this study were the primary data and the secondary data. The primary data obtained by using a quesionnaire with student respondent totaling 93 people and the secondary data obtained by using pre research and documentation data. This study used purposive sampling technique. The result or the study shows that entrepreneurship learning positively dan significantly affects entrepreneurship interest of student, indicated by tobtained =11,035 with significance value of 0,000 and R2 = 0,572.